Autoavaliação da saúde em adolescentes e adultos: estudo saúde em Beagá - Adriana Lucia Meireles (2014)
Introduction: The self-rated health (SRH) focuses on the subjective perception of health and is related to well-being and life satisfaction. Objective: To know the self-rated health and its associated factors among adolescents and adults living in Belo Horizonte, Minas Gerais. Methods: We used data from Saúde em Beagá Study, a population-based household survey. This survey was conducted by the Observatory for Urban Health in Belo Horizonte, between 2008 and 2009 in Belo Horizonte, and it included 1,042 adolescents and 4,048 adults. The outcome variable was the SRH categorized in poor (fair, poor or very poor) and good (very good and good). Multivariate models (logistic regression for adolescents and Poisson robust models for adults) were used to evaluate the association between poor SRH and explanatory variables. Results: Regarding the adolescents, about 11% (95%CI: 8.7-13.6) of the adolescents reported poor SRH and worse this perception increased with age in both sexes. However, this increase was more pronounced in girls (6.9% of 11-13 years to 16.9% for 14-17 years) than in boys (8.3% of 11-13 years to 11 % of 14 - 17 years). In both age groups, family support were associated with poor SRH. Family support was measured by family structure and reporting the existence of fights to adolescents of 14-17 years and the absence of discussion with parents to adolescents 11 to 13 years. Among older teens, unhealthy lifestyles (OR = 2.4), dissatisfaction with life (OR = 2.8) , low birth weight (OR = 6.7) and overweight (OR = 2.7) also joined the AAS bad when compared to their peers . The results of the adults showed an overall prevalence of 29.9% of poor SRH (95% CI: 28.0 - 31.9); in those with morbidity of 42.6% (95% CI: 40.2 - 45.0%) and in the group without morbidity of 13.1% (95% CI: 10,9 - 15,3%). Perceived problems in the home environment were associated with poor SRH in both groups investigated, even after adjustment hierarchical, and sociodemographic variables that make up the fields, lifestyles and psychological health. The domain Anthropometry and Use of Health Services was only associated with the SRH in morbidity group. Conclusions: The SRH is a multidimensional construct, influenced by individual and environmental factors, and these findings are supported by national and international studies. The results suggest that when using the SRH as single-item measure for overall health assessment is critical considering the age and the reports of diseases. Our findings also reinforce the need for inclusion of variables that characterize physical and social environment in the study of subjective assessment of health of individuals living in urban areas.